AN INVESTIGATION INTO CONTENT LANGUAGE INTEGARTED LEARNING IN THE NEW ENGLISH TEXTBOOKS A CASE STUDY AT LÊ QUÝ ĐÔN HIGH SCHOOL = ĐIỀU TRA VỀ NỘI DUNG TÍCH HỢP NỘI DUNG VÀ NGÔN NGỮ TRONG SÁCH GIÁO KHOA TIẾNG ANH MỚI – NGHIÊN CỨU TẠI TRƯỜNG THPT LÊ QUÝ ĐÔN - Trần, Hiền Anh (2020)
Since 2016, the new English textbooks have been experimented in six classes at Lê Quý Đôn high school. Culture, which is the brand new part in the new textbooks, has applied content language integrated learning program. To the researcher’s belief, as the outcomes of content language integrated learning in the new textbook have not been proved yet, the perceptions of stakeholders: teachers and students to this section have stood out asone of the issue that need to be studied. Being one of the first to investigate this under - researched population, this study looks at teachers and students’ perceptions of content language integrated learning as well as their benefits and challenges while applying these contents. By employing survey questionnaires and semi - structured interviews, the researcher wishes to find out teachers and students’ points of view of content and language integrated learning and some benefits and challenges that they are having. Analysis of data collected from 267 students and 3 teachers who are studying and teaching in 6 classes: 10A1, 10D1, 11A1, 11D1, 12A1 and 12D1 at the beginning of the second semester year 2017 – 2018 has revealed that both teachers and students hold positive views toward content language integrated learning in the new English textbooks. Moreover, teachers’ greatest benefit from content and language integrated learning is students’ motivation and engagement but they also have always encountered with time limitation and students’ low English levels. In addition, while improving cultural appropriateness and context appears to be students’ most enormous gain, the difficulty that they are facing is unqualified teachers, in other words, wrong teaching methods. Findings of the study might be considered as one of the references for Ministry of Education and Training, textbooks’ writers and English teachers to edit and adapt the new textbooks to cater for all students’ needs and abilities. Appropriate action for further improvement of the new textbooks and teaching quality in the future is suggested at the end of the paper.